Level of attitude toward complementary and alternative medicine among Iranian patients with multiple sclerosis - Harirchian, Mohammad Hossein (Tehran University of Medical Sciences, 2014)
BACKGROUND: Multiple sclerosis (MS) is an unpredictable neurological disease leading to severe disability in young adults. The majority of MS patients use complementary and alternative medicine (CAM) as adjunct to conventional therapies. This study aimed to investigate the prevalence of CAM utilization among Iranian patients with MS and their attitude toward the CAM usage. METHODS: A cross-sectional study was conducted on 119 definite MS patients referred to Tehran’s Imam Khomeini and Sina hospitals. A questionnaire was used to examine the association between participants’ health-related factors and usage of CAMs interventions. P value < 0.05 was considered statistically significant. RESULTS: Among the enrolled patients, 60% of the participants agreed with using CAM, 42% experienced the usage of these treatments; out of whom 41% believed its efficiency and 18% reported exacerbation of symptoms. The mean duration of disease diagnosis and mean time from symptoms onset were both longer in users of CAM (P = 0.001). Most socio-demographic factors had no significant effect on the type of used CAM. However, Yoga was significantly more applied in those with higher degree of education (P = 0.002). CONCLUSION: Regarding the widespread use of CAM by Iranian patients with MS, further researches about the safety and efficacy of each treatment on the special outcomes is recommended.